2021
DOI: 10.1016/j.amsu.2021.102641
|View full text |Cite
|
Sign up to set email alerts
|

Early initiation of awake venovenous extracorporeal membrane oxygenation (ECMO) in critical COVID-19 pneumonia: A case reports

Abstract: Introduction Overall, patients with Sars-cov-2 disease treated with mechanical ventilation, which is not the case in our study. This report presents our first successful experience of awake ECMO application in a critical patient with hypoxemic Respiratory Failure related to COVID-19 infection in Morocco. Case management We have reported a 52-year-old female patient who was diagnosed with COVID-19 infection and progressed to critical cases. She was a candidate for applyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…A total of 57 articles including data from 467 awake ECMO patients (923 total ECMO patients) were included in the analysis ( Fig. 1 ) (21–73). Of these, 28 articles (49%) were case reports including a single patient each and 29 articles (51%) were case series with a median sample size of 10 patients (range, 3–65 patients) ( Supplementary Table 1 , http://links.lww.com/CCM/H411).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 57 articles including data from 467 awake ECMO patients (923 total ECMO patients) were included in the analysis ( Fig. 1 ) (21–73). Of these, 28 articles (49%) were case reports including a single patient each and 29 articles (51%) were case series with a median sample size of 10 patients (range, 3–65 patients) ( Supplementary Table 1 , http://links.lww.com/CCM/H411).…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective case series describing eight cases where awake vv-ECMO was applied in COVID-19 patients with severe ARDS found a mortality rate of only 14.3% (1 patient) [12]. Other single case reports also showed promising results [13][14][15]. However, a prospective observational trial on four German ICUs found that out of 18 patients that were treated with awake vv-ECMO implantation, 14 were intubated during the further stay on ICU [16].…”
Section: Discussionmentioning
confidence: 99%
“…ECMO is a type of membrane oxygenator application used as life support in patients suffering from acute heart, lung, or cardiopulmonary failure [ 11 , 12 ]. This device is used when mechanical breathing fails and there is not enough time to treat the underlying pathology [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%